The novel glycyrrhetinic acid–tetramethylpyrazine conjugate TOGA induces anti-hepatocarcinogenesis by inhibiting the effects of tumor-associated macrophages on tumor cells. (November 2020) - Wang, Xue; Tan, Yan; Zhang, Yali; Xu, Zihui; Xu, Bing; Lei, Haimin; Ding, Chengcheng; Cheng, Shuo; Wang, Xu; Wei, Peng; Wang, Zhaoyang; Mao, Qiantai; et al.
Graphical abstract: Abstract: Hepatocellular carcinoma (HCC), with its high recurrence and metastasis rates, is a leading cause of cancer-related mortality, and available treatments include surgical resection and liver transplantation. TOGA is a novel conjugate combining 18β-glycyrrhetinic acid (GA), an active component of licorice, and tetramethylpyrazine, an effective component of Chuanxiong, with a small-molecule amino acid. This study examined the anti-hepatoma effects of TOGA and its specific mechanisms of action. We found that TOGA significantly prevented tumor growth in both nude mice carrying liver cancer xenograftsand mice carrying orthotopic tumors with little toxicity. NanoString analysis screening illustrated that TOGA may exert its anti-tumor effects by targeting interleukin (IL)-1R receptor 1 (IL-1R1). Further, TOGA significantly prevented the invasion and migration of HepG2 cells induced by tumor-associated macrophages (TAMs) or IL-1β, as confirmed by the reduced expression of the epithelial-mesenchymal transition (EMT)-related proteins Snail and Vimentin. Furthermore, IL-1β-induced activation of the IL-1R1/IκB/IKK/NF-κB signaling pathway in HepG2 cells was proved to be inhibited by TOGA. Taken together, TOGA effectively prevents the support of TAMs from fueling tumorigenesis through a mechanism related to the NF-κB pathway, and it may be a promising GA-modified drug for the treatment of HCC.